Francis Alÿs - ricochets - Ostende, Florence 1983- (Prestel, 2024)
This immersive publication explores the artistic journey of one of today’s most prominent conceptual artists, with a specific focus on his groundbreaking series, Children's Games. Whether he’s moving a sand dune in Peru or pushing an enormous ice block through the streets of Mexico City, Francis Alÿs is constantly seeking to decipher complex social, political, and cultural issues in ways that are simultaneously affecting, imaginative and provocative. Highlighting rarely seen source material, this richly illustrated book delves into the impulses behind Alÿs’s influential works. Celebrating the breadth and importance of the artist’s work, a series of essays by leading scholars and writers look at his studio practice and influences across art, history and literature, revealing new perspectives on his prolific career and ongoing preoccupations. It also examines the most recent iteration of his critically acclaimed series Children’s Games, in which he documents children’s games from various cultures around the world. From whimsical explorations of everyday life to his engagement with cross-cultural contexts from Latin America to North Africa and the Middle East, Alÿs’s work serves as a platform for navigating the world, inviting viewers to engage with the poetic and transformative potential of artistic expression
Impressum: First published in 2024 by Prestel Verlag in association with Barbican Art Gallery and Serralves Foundation on the occasion of the exhibition: "Francis Alÿs: Ricochets", Barbican Art Gallery, 27 June - 1 September 2024; Serralves Museum of Contemporary Art, 24 October 2024 - 16 March 2025
Keywords: Alÿs, Francis -- 1959-; Kinderspiel; Spiel; Öffentlicher Raum; Dokumentationsprojekt; Ausstellungskatalog -- Barbican Art Gallery -- 27.06.2024-01.09.2024 -- London; Ausstellungskatalog -- Museu de Arte Contemporânea de Serralves -- 24.10.2024-16.03.2025 -- Porto, Portugal